2023
DOI: 10.1371/journal.pone.0285628
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain-derived neurotrophic factor (BDNF) and self-paced time-trial performance in older untrained men

Abstract: Purpose This study examined the effect of 12 weeks of concurrent aerobic and resistance training on brain derived neurotrophic factor (BDNF) levels, neuromuscular performance and cerebral oxygenation on self-paced cycling exercise in previously untrained older men. Methods Eight untrained healthy males aged 53–64 years performed a familiarisation and a pre-training self-paced cycling time trial before 12 weeks of exercise training which combined aerobic and resistance exercise. The self-paced cycling time tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Physical activity is posited to have protective effects against psychiatric symptoms and cognitive decline through multiple biological and psychosocial mechanisms. One primary biological pathway involves the upregulation of neurotrophic factors, notably brain-derived neurotrophic factor (BDNF), which plays a critical role in neuronal survival, neuronal development, and synaptic plasticity ( Chia & Marino, 2023 ). Furthermore, physical activity has been implicated in the stimulation of neurogenesis, particularly in the hippocampal region, which is integral to memory and learning ( Pahlavani, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is posited to have protective effects against psychiatric symptoms and cognitive decline through multiple biological and psychosocial mechanisms. One primary biological pathway involves the upregulation of neurotrophic factors, notably brain-derived neurotrophic factor (BDNF), which plays a critical role in neuronal survival, neuronal development, and synaptic plasticity ( Chia & Marino, 2023 ). Furthermore, physical activity has been implicated in the stimulation of neurogenesis, particularly in the hippocampal region, which is integral to memory and learning ( Pahlavani, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found no increase in resting serum BDNF levels after six months of aerobic training, resistance training, or their combination in adolescents with overweight and obesity [ 168 ]. In contrast, healthy males aged 53 to 64 years demonstrated a reduction in BDNF serum levels following 12 weeks of aerobic and resistance training [ 169 ]. On the other hand, healthy older individuals experienced a significant immediate increase in serum BDNF levels following a 35-min physical exercise session [ 170 ].…”
Section: Discussionmentioning
confidence: 99%